PERKEMBANGAN BAHASA ANAK USIA DINI DAN PENGEMBANGANNYA DI SEKOLAH - Syauqia, Dina Zuhda; Istiqomah, Ani Sofiana; Munawaroh, Hidayatu (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
Early Aged Children Education (EACE) is a part ofpreshool education. The matter ofthe education, particularly, has been drawn up in government regulation 2003 in the point 28 part I. The regulation stated that EACE is conducted before the elementary education. In developing a language, the teacher needsto have·aknowledge ofthe language development and he developing oflanguage. Children'slanguage developmenttest inthe periodes. The fIrst periode is the pre-lingustic periode which are 0-2 months ofphonation stage in which children learn pronounce the vocal symbols, 2-4 months ofgoing stage, 4-7 months ofexpansion stage in which children begin to produce some new sounds, 7-10 months of cononical stage, 10-14 months of contractionstage in wihchchildren leamto imitate same soundthey listen to. The second isthe linguistic period. It includes 12month children in holofrase periode in which children are able to express a sentence consisting of3-6 words, 2-3 year childrenmay use the widernouns with the vocabulary of3-50 words, 3 year children have vocabulary of 200-300 words. 4 year children are able to use a langusge with the correctstucture and with the vocabulary of1400-1600words. 5-6 year children have a correct order of language. The technique ofdeveloping language in schools can be: (a) maximizing natural communication for children, (b) considering the silent period on the early ofthe learning program, (c) using the concrete reference so that 2nd language can be comprehendedby children,(d) using themeaning fuul phrase when the teacher is teaching dialogues, (e) avoiding teaching structure to children, (t) avoiding retenng the LI when teaching L2